A Study to Determine the Incidence and Prevalence of Newly Discovered Human Immunodeficiency Virus Infection During the Prenatal Care Period. Issue 3 (2000) - Grimes, Richard M.; Srivastava, Geetanjali; Helfgott, Andrew W.; Eriksen, Nancy L.
Abstract : Objectives: This study asked the following questions: 1) Does HIV testing in pregnancy identify women who previously were not known to be HIV positive? 2) When in pregnancy are women identified as HIV infected? 3) Does HIV seroconversion occur during the prenatal care period? Methods: Medical records of 97 women from two primarily indigent care hospitals in Houston, TX who were found to be HIV positive at delivery were reviewed to determine if they had tested positive during the prenatal care period. Demographics and time of gestation of the prenatal testing also were recorded. The outcome measures were: 1) number of women found positive during prenatal care; 2) week of gestation at discovery of HIV positivity; and 3) number of women seroconverting between the initiation of prenatal care and delivery. Results: Thirty women were known to be HIV positive prior to pregnancy. Fifty-six women were found to be positive during prenatal care and the seropositivity of 44 was discovered before the 34th week of pregnancy. Ten women were found to be positive at their first prenatal visit, which occurred after the 34th week. Date of testing was unknown for two women. Eleven women who received no prenatal care were found to be HIV positive at delivery. There were no seroconversions while women were under prenatal care. Conclusions: HIV testing at delivery did not find any HIV-positive women who had tested negative during prenatal care. Testing is very important for women who do not receive prenatal care. Making certain that high-risk women get into prenatal care also is very important. Infect. Dis. Obstet. Gynecol. 8:172–175, 2000.